Comparative evaluation of chlorhexidine gluconate with alcohol and polyhexamethylene biguanide with Tris-EDTA as antiseptic solutions for pre-operative skin preparation in dogs - Nithida Boonwittaya; Chompoonek Yurayart; Pareeya Udomkusonsri; Saroch Kaewmanee; Somchai Sompaisarnsilp; Naris Thengchaisri; Taksaon Duangurai (Veterinary World)
Background and Aim: Skin antisepsis plays a crucial role in pre-operative skin preparation, with chlorhexidine gluconate and alcohol being historically the preferred choice. However, concerns have risen regarding the development of bacterial resistance to chlorhexidine. Polyhexamethylene biguanide (PHMB) combined with Tris-ethylenediaminetetraacetic acid (Tris-EDTA) has recently emerged as a skin and wound antiseptic. This study aimed to compare the antibacterial efficacy and local safety of 2% chlorhexidine gluconate with 70% alcohol (CG+Alc) and 0.3% PHMB with 6% Tris and 1.86% EDTA (PHMB+Tris-EDTA) for pre-operative skin preparation in dogs.